Immune targeted therapy for diffuse large B cell lymphoma - Yaxin Zheng (Wolters Kluwer Health, 2021)
Abstract. Diffuse large B-cell lymphoma (DLBCL), the most common subtype of non-Hodgkin lymphoma, is highly heterogeneous and invasive. Although the majority of DLBCL patients show a good response to rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone treatment, approximately one-third of patients still have a poor prognosis. Many immune-targeted drugs, such as bispecific T-cell engagers and CAR T-cell therapy, have been proven effective for refractory and relapsed patients. This article reviews the progress of immune targeted therapy for DLBCL.